Biochar and Bacillus subtilis co-drive dryland soil microbial community and enzyme responses - Zheng, Tao; Huang, Xianhuai; Zhou, Xiaoyu; Wu, Jizi; Kamran, Muhammad Aqeel; Yu, Xiongsheng; Qian, Jing (Frontiers in Microbiology, 2025)
IntroductionTo investigate the impact of soil amendments on the structure of the soil microbial community.MethodsThis study focuses on dryland soil and employs indoor static cultivation as the experimental approach. It analyzes the impact and mechanism of adding rice straw biochar (S), rapeseed straw biochar (Y), and Bacillus subtilis agent (J) separately and in combination on the soil microbial community structure.ResultsThe experimental results indicated that, compared to the blank control (CK), the Y treatment increased the relative abundance of Proteobacteria by approximately 3.03% and significantly reduced the abundance of Acidobacteria (from 70.56% to 82.81%). The application of biochar and microbial inoculants significantly increased the relative abundance of Ascomycota (2.85% to 33.53%) and Rozellomycota (0.58% to 27.73%). Furthermore, the addition of soil amendments enhanced the richness (3.02% to 7.07%) and diversity (3.22% to 3.77%) of soil bacteria, as well as the microbial nitrogen content (3.7 to 9.3 times). Meanwhile, except for the YJ treatment, the richness of the fungal community decreased, while the diversity index increased. The experimental results showed that the application of rapeseed straw biochar or the compound microbial inoculant alone significantly increased soil urease activity, reaching 40.34 µg of NH+4-N g−1 of soil h−1 and 40.29 µg of NH+4-N g−1 of soil h−1 at the end of the incubation period, respectively.DiscussionIn conclusion, rapeseed straw biochar not only enhances the soil microbial community but also significantly influences soil enzyme activity. This study offers a scientific foundation for utilizing biochar and Bacillus subtilis to improve dryland soil, providing valuable insights for sustainable soil management.